Common and Challenging Behaviors Among Individuals on Long-term Opioid Therapy. Issue 4 (July 2020) - Young, Sarah R.; Azari, Soraya; Becker, William C.; Edelman, E. Jennifer; Liebschutz, Jane M.; Roy, Payel; Starrels, Joanna L.; Merlin, Jessica S.
Abstract : Objective: Long-term opioid therapy (LTOT) is commonly prescribed for chronic pain, despite risks such as opioid use disorder (OUD) and overdose. Caring for patients on LTOT can be difficult, given lack of evidence about assessment of challenging behaviors among patients on LTOT. To develop this evidence, a critical first step is to systematically identify the common and challenging behaviors that primary care providers encounter among patients on LTOT, and also to highlight to diverse range of behaviors encountered. Method: We conducted a Delphi study in 42 chronic pain experts to determine consensus on how to address the top common and challenging behaviors. This paper reports on the first round of the study, which elicited a range of behaviors. We conducted thematic analysis of the behaviors and also used the Diagnostic and Statistical Manual (DSM)-5 criteria for OUD as a priori codes. Results: In all, 124 unique behaviors were identified by participants and coded into 4 thematic categories: concerning behaviors that map onto DSM-5 criteria for OUD, and those that do not which were: behaviors that suggest deception, signs of diversion, and nonadherence to treatment plan. Those behaviors that fell outside of OUD criteria we identified as "gray zone" behaviors. Conclusions: While some of these challenging behaviors fall under the criteria for an OUD, many fall outside of this framework, making diagnosis and treatment difficult, and consensus on how to deal with these "gray zone" behaviors is vital. Future research should explore how these "gray zone" behaviors can best be assessed and managed in a primary care setting. Abstract : Supplemental Digital Content is available in the text